Home Office response to the Independent Chief Inspector of Borders and Immigration’s report : An Inspection of the Home Office’s Network Consolidation Programme and the “onshoring” of visa processing and decision making to the UK.: An Inspection of the Home Office’s Network Consolidation Programme and the “onshoring” of visa processing and decision making to the UK. (2020) - Unknown
No abstract available